Recent Developments in Financial Innovation Research and Sustainable Accounting Models Bibliometric Analysis approach - Judijanto, Loso; Sudarmanto, Eko; Kalsum, Ummu; Iskandar, Deni (The Es Accounting And Finance, 2024)
This study conducts a systematic bibliometric analysis to examine recent developments in financial innovation research and sustainable accounting models. The intertwining of financial innovation and sustainability reflects a significant shift in the global economic paradigm, with innovations such as green bonds and impact investing reshaping financial markets. The research aims to identify key themes, trends, and interdisciplinary connections within the literature, offering insights for academia, practitioners, policymakers, and other stakeholders. Analysis reveals a growing emphasis on the role of financial innovation in driving sustainable growth and the importance of sustainable accounting in fostering transparency and accountability. The study also highlights emerging research directions, including interdisciplinary approaches, drivers of innovation and development, microfinance impact on household economics, and the nexus between education and health. Ultimately, this research seeks to contribute to the advancement of knowledge and practices promoting both financial prosperity and environmental and social well-being.